2021
DOI: 10.1136/bmjopen-2021-052826
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health promotion messages for young people in Netflix most-watched series content (2015–2020): mixed-methods analysis study

Abstract: IntroductionSexual health is a major issue for young people, and there is a need to promote it. Sexual health promotion messages may be included in Netflix series that are widely watched by young people, with important emotional dimensions in scenarios.ObjectiveThe aim of this study is to investigate the explicit sexual health promotion messages integrated in Netflix series popular among young people, and to describe them and how they are delivered.MethodsWe selected two types of Netflix series, aimed at young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In an era of mediating consent and promoting empathy in sex education [31], this would enable adolescents without chronic diseases to better understand the experiences and constraints of illness and treatment. Following the example of the educational series for teenagers "Sex Education" on the Net ix platform, which addresses topics such as sexual orientation or sexual dysfunction, we could envisage including protagonists with chronic diseases who nd positive outcomes in their love and sex lives [32].…”
Section: Discussionmentioning
confidence: 99%
“…In an era of mediating consent and promoting empathy in sex education [31], this would enable adolescents without chronic diseases to better understand the experiences and constraints of illness and treatment. Following the example of the educational series for teenagers "Sex Education" on the Net ix platform, which addresses topics such as sexual orientation or sexual dysfunction, we could envisage including protagonists with chronic diseases who nd positive outcomes in their love and sex lives [32].…”
Section: Discussionmentioning
confidence: 99%
“…This would enable adolescents without chronic diseases to better understand the experiences and constraints of illness and treatment in the contemporary era of mediating consent and promoting empathy in sex education [ 44 ]. Following the example of the educational series for teenagers “Sex Education” on the Netflix platform, which addresses topics such as sexual orientation and sexual dysfunction, we could envisage including protagonists with chronic disease (visible or not) who experience positive outcomes in their romantic relationships and sexual activity [ 45 ]. It would also be relevant to include testimonies from adolescents with chronic diseases in existing programs like those supported by the Population Council (an international, non-profit, non-governmental organization) [ 46 ] and Santé Publique France (a national agency under the Ministry of Health) [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, a recent study examining sexual health promotion messages integrated in Netflix series popular among young people found that 62 messages were incorporated in their sample of 6 series and these messages focused on sexual harassment and violence (19%), on sexually transmitted infections protection (18%), and on contraception (15%). 34 Finally, in reference to alcohol and cigarette use, a recent study exploring alcohol and tobacco content in a sample of 5 video-on-demand programs (50 episodes) determined that 74% of episodes depicted tobacco content and 94% of episodes depicted alcohol content. 35 Although negative themes, such as violence, sexuality, and alcohol/cigarette use, were not commonly depicted in our sample of TV shows, we encourage the promotion of associated positive themes, such as "demonstrating teamwork," "demonstrating forgiveness," "abstaining from peer pressure," "learning from past mistakes," and "proper exercise/ nutrition (taking care of one's body).…”
Section: Discussionmentioning
confidence: 99%